PROFESIONALISME GURU DALAM UPAYA MENINGKATKAN MUTU PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN IHYAUL ULUM PURBASINOMBA - Syaipuddin Ritonga (AL MA'ANY, 2022)
The teacher is part of an important component in the learning process. Professional teachers are teachers who have broad competencies who master all the elements in learning such as mastery of learning materials, methods, strategies and necessary learning steps. Learning Arabic is a basic learning that is characteristic of Islamic boarding schools, so learning Arabic is the main focus in learning materials. Professional Arabic teachers are characterized by teachers who can carry out learning well and can achieve the goals that have been formulated previously while being able to produce students who have Arabic language skills according to the level and class of student learning. The purpose of this research is to be able to understand what are the indicators of backwardness and backwardness in learning at the Ihyaul Ulum Islamic Boarding School in Purbasinomba so that it can provide ideas and suggestions as well as suggestions for improving the professionalism of Arabic teachers in order to build and develop the quality of existing learning. The method used in this research is descriptive qualitative research by observing and concluding information from the Head of the Islamic Boarding School, teachers, students and the ongoing learning process. The results obtained by Arabic Learning Teachers are still far from professional, starting from academic qualifications, mastery of learning materials to managing the learning process, so it is necessary to improve and improve the professionalism of Arabic teachers in various ways of professional development such as training, upgrading, workshops/ seminars and the addition of other supporting facilities and infrastructure in order to improve the quality and quality of learning.